Prevención del suicidio en contextos digitales - Vaca Jaramillo, Jorge Antonio (My University, 2025)
With the aim of analyzing the scientific evidence on digital technologies and artificial intelligence in suicide prevention through a systematic review, the PRISMA methodology was applied by consulting five academic databases (Web of Science, Scopus, PubMed, Science Direct, EBSCO) using specific Boolean operators. Out of 600 initial records, 40 studies (2020-2025) were selected after applying inclusion/exclusion criteria. The results indicate that the identified technologies include therapeutic chatbots, large language models, machine learning algorithms, and social media analysis. They showed effectiveness in early detection, psychoeducational intervention, and emotional support in diverse populations (adolescents, adults, veterans). Conclusions establish that digital technologies and AI present significant potential for suicide prevention, requiring rigorous clinical validations and ethical frameworks for safe implementation.
Con el objetivo de analizar la evidencia científica sobre tecnologías digitales e inteligencia artificial en prevención del suicidio mediante revisión sistemática. Se aplicó la metodología PRISMA consultando cinco bases de datos académicas (Web of Science, Scopus, PubMed, Science Direct, EBSCO) con operadores booleanos específicos. De 600 registros iniciales, se seleccionaron 40 estudios (2020-2025) tras aplicar criterios de inclusión/exclusión. Los resultados señalan que las tecnologías identificadas incluyen chatbots terapéuticos, modelos de lenguaje grandes, algoritmos de aprendizaje automático y análisis de redes sociales. Mostraron efectividad en detección temprana, intervención psicoeducativa y apoyo emocional en poblaciones diversas (adolescentes, adultos, veteranos). Conclusiones establecen que las tecnologías digitales e IA presentan potencial significativo para prevención del suicidio, requiriendo validaciones clínicas rigurosas y marcos éticos para implementación segura
Keywords: PREVENCIÓN DEL SUICIDIO; INTELIGENCIA ARTIFICIAL; DETECCIÓN TEMPRANA; IDEACIÓN SUICIDA